REPRESENTASI KESETARAAN GENDER DALAM DUNIA KERJA (STUDI KASUS PADA STASIUN PAL TV PALEMBANG): Studi Kasus Pada Stasiun PAL TV Paembang - Permata, Shania Suly; Yenrizal; Astrid, Gita (Jurnal Prodi Ilmu Komunikasi, 2024)
Gender equality is basically the same in all walks of life. God created male and female humans to be the same because they are the highest form of life on earth. However, sometimes there are several things that make the low role of women in life that often occurs, including in the world of work such as television stations, women's expectations for their role in society have shifted due to technological changes and globalization, many women have been proven to be able to lead their own lives in the world and leave the house. to pursue their interests outside the home is what can further their own professional and personal development as women. And it is believed to have a significant influence on the tendency of female television workers to represent the lack of women in the world of work. This research was conducted qualitatively directly at PAL TV Palembang Station. Respondents in this study were the main sources of women who worked in the PAL TV media industry. Functional Structural Theory explains that there are 3 elements that play an important role in this theory, namely: division of labor according to needs, function of social structure, and system of social structure. Which shows that the majority of women at the PAL TV Palembang station still feel that there is gender inequality in the world of work which they experience such as promotion and leading at every event. The purpose of this research is to find out whether it is true that in the PAL TV station there are employees who feel gender inequality. By proving the existence of this research, the researchers hope that there will be equality for women and men workers at the PAL TV station so that they can reconsider the things that are the root of the problem in this research.